2017
DOI: 10.4330/wjc.v9.i5.442
|View full text |Cite
|
Sign up to set email alerts
|

Jailing polymer jacketed guide-wires during bifurcation coronary interventions is associated with procedural myocardial infarction

Abstract: AIMTo study the relationship of jailed polymer jacketed guide wires (PGW) with procedural myocardial infarction (PMI) after bifurcation coronary interventions.METHODSConsecutive bifurcation interventions performed from January 2010 to October 2014 were included in the study. Chart review was performed to obtain demographic, clinical and procedural data. PMI was defined as Creatine Kinase MB > 3 × upper reference limit of normal. Multivariate logistic regression was used to ascertain relationship of PGW use wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Polymer-coated wires were more resistant to retrieval damage and were more efficient in crossing the SB ostium than nonpolymer-coated wires, 23 but another study reported that jailed polymerjacketed guidewires were associated with procedural MI. 24…”
Section: Distal Lesions Wiringmentioning
confidence: 99%
“…Polymer-coated wires were more resistant to retrieval damage and were more efficient in crossing the SB ostium than nonpolymer-coated wires, 23 but another study reported that jailed polymerjacketed guidewires were associated with procedural MI. 24…”
Section: Distal Lesions Wiringmentioning
confidence: 99%